2022
DOI: 10.1186/s13046-021-02223-y
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin triggers breast cancer cell death via fatty acid metabolic reprogramming

Abstract: Background Adiponectin, the most abundant adipokine derived from adipose tissue, exhibits a potent suppressive effect on the growth of breast cancer cells; however, the underlying molecular mechanisms for this effect are not completely understood. Fatty acid metabolic reprogramming has recently been recognized as a crucial driver of cancer progression. Adiponectin demonstrates a wide range of metabolic activities for the modulation of lipid metabolism under physiological conditions. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 68 publications
2
23
0
Order By: Relevance
“…We noticed that the genomic difference exhibited a significant correlation with cancer or cell cycle-related pathways, including metabolic pathways, transcriptional mis-regulation, and fatty acid biosynthesis. These findings were consistent with some earlier prior studies in which the presence of aberrant transcription (37) or fatty acid metabolic reprogramming (38) was ascertained to be a crucial driver of breast cancer progression. The PPI network further introduced the top twenty molecules, which exhibited substantially close interactions in breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…We noticed that the genomic difference exhibited a significant correlation with cancer or cell cycle-related pathways, including metabolic pathways, transcriptional mis-regulation, and fatty acid biosynthesis. These findings were consistent with some earlier prior studies in which the presence of aberrant transcription (37) or fatty acid metabolic reprogramming (38) was ascertained to be a crucial driver of breast cancer progression. The PPI network further introduced the top twenty molecules, which exhibited substantially close interactions in breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…Cell viability assay was carried out as described previously ( Pham and Park 2022 ). In brief, Raw 264.7 cells were seeded in 96-well plates at the density of 5×10 4 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…In the same concept, an in vivo study showed that adiponectin treatment inhibits leptin-induced mammary tumorigenesis in nude mice by suppressing two canonical signaling molecules, extracellular signal-regulated kinase (ERK) and Akt [ 42 ]. Furthermore, a recent study showed that globular adiponectin induces tumor suppression by decreasing the cellular lipid pool, mainly through the inhibition of fatty acid synthase (FAS) and the activation of Sirtuin 1 (SIRT-1), which will promote apoptosis in vivo and in vitro [ 78 ].…”
Section: The Involvement Of Adiponectin In Breast Cancermentioning
confidence: 99%